PATIENTS WITH ATRIAL FIBRILLATION AND ISCHEMIC HEART DISEASE: HOSPITALIZATION STRUCTURE AND ANTITHROMBOTIC THERAPY (RECVASA AF-KURSK REGISTRY) - V. P. Mikhin; Yu. V. Maslennikova; M. M. Loukianov (SINAPS LLC, 2017)
Study objective. To assess the peculiarities of hospitalization of patients with AF in combination with CHD in the departments of the general therapeutic profile of a multidisciplinary hospital, the frequency of complications of various forms of AF, to analyze anticoagulant (AC) and antiplatelet (AP) therapy in prehospital (PreH), hospital and post-hospital (PostH) stages of treatment based on the register. Material and methods. 502 patients were included in the prospective hospital registry RECVASA AF-Kursk, 480 of which with the diagnosis of AF in combination with ischemic heart disease were hospitalized in the therapeutical departments of Kursk Emergency Hospital during the period from 01.06.2013 to 31.05.2014. 2-3 years after the referral hospitalization, information about the drugs taken was collected after telephone or face-to-face contact with survived patients (n = 293), as well as their relatives, treating doctors. Results. The study included 261 women and 219 men, with an average age of 70.4 ± 10.3 years. The greatest number of patients with AF was treated in the departments of cardiology and therapy. In all departments, patients with a permanent AF prevailed, with the exception of cardiology, where the proportion of patients with persistent AF was the greatest. The share of stroke and MI was 39.4% and 29.8%, respectively. The cases of emergent hospitalizations recorded 56.8%, 28.6% of them - because of the AF. Among patients with different forms of AF, there were no differences in the frequency of emergent hospitalizations (p>0.05). The polyclinic directed 38% of patients, 41% of AF (p = 0.007). In all cases, the main cause of the hospitalization was cardiovascular disease (CVD). In patients with AF and IHD, prognostically significant AC therapy at the outpatient stage was assigned in 5.3%. By the time of discharge from hospital, the frequency of application of AC increased to 26.5% (p = 0.0001); Among patients with a permanent AF, AC are used significantly more often - in 30% of cases, in comparison with other forms of AF. At the PH stage, there remains a low share of AC (20%). At the same time in 20% of the PreH stage, 74.2% at the time of discharge and 64.5% of the cases at the PostH stage, instead of AC, AP were unreasonably prescribed. Conclusion. According to the prospective registry RECVASA AF-Kursk patients with AF in combination with IHD are hospitalized in the hospital, mainly because of CVD, half of them for emergent indications. Stroke and MI in this category of patients reaches a third of cases. There is a low frequency of prescribing ACat all stages of treatment (5.3% in PreH, 26.5% at discharge and 20.2% in PostH stages), unjustifiably replaced with AP therapy. At the hospital and PostH stages, significantly more frequent use of both AC and AP is observed in comparison with the PreH stage.